SEZ6L2 Antibody-Associated Cerebellar Ataxia Responsive to Sequential Immunotherapy - Mehdiyeva Ayla; Hietaharju Aki; Sipilä Jussi (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objectives Seizure-related 6 homolog like 2 (SEZ6L2) antibody-associated ataxia is an extremely rare disease. Six patients have been reported and none of them improved significantly with immunotherapy. Herein, we present the case of a patient with cerebellar ataxia and SEZ6L2 antibodies who benefited from immunotherapy, which dramatically altered the course of her disease.
Methods We present a case report of a 73-year-old woman with progressive balance problems. Her condition had rapidly deteriorated in the 2 weeks before the admission to our hospital leading to repeated falls and eventually left her bed-ridden.
Results She presented with severe trunk ataxia, bidirectional nystagmus, dysarthric speech, and persistent nausea. With the exception of cerebellar atrophy, extensive imaging studies revealed no pathology. SEZ6L2 antibodies were found in both CSF and serum. Over a period of 9 months, our patient received immunotherapy consisting of steroid pulse therapy, IV immunoglobulin infusions, rituximab, and cyclophosphamide. Consequently, her condition improved markedly, and she was discharged home from the neurologic rehabilitation unit.
Discussion Our case report shows that intense sequential immunotherapy may considerably improve level of functioning in some patients with SEZ6L2 antibody-associated cerebellar ataxia.
Classification of Evidence This provides Class IV evidence. It is a single observational study without controls.